PENGEMBANGAN SOAL Higher Order Thinking Skill (HOTS) TIPE PILIHAN GANDA DENGAN SISTEM PENILAIAN ACUAN NORMA (PAN) PADA MATERI SISTEM GERAK DI SMA NEGERI 6 PALEMBANG - Nazlan Hafidz Basran; Mini Sariwulan; Asnilawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The choice of the research location at SMA Negeri 6 Palembang was based on the results of an interview with the Biology MGMP of Palembang City on August 8, 2025, which recommended the school because it has already implemented HOTS questions and is more easily accessible compared to other schools. Furthermore, an initial observation on September 17, 2025, confirmed that SMA Negeri 6 Palembang had applied HOTS questions, although the implementation was not yet optimal since most questions were still at cognitive levels C1–C3. This study aims to develop a multiple-choice Higher Order Thinking Skills (HOTS) question instrument using a Norm-Referenced Assessment (NRA) system on movement system material at SMA Negeri 6 Palembang, as well as to determine its validity and effectiveness. This study used a Research and Development (R&D) method with a 4D development model (define, design, develop, disseminate), but was limited only to the development stage (develop). The research subjects consisted of 36 students from class XI.1, with sampling done using purposive sampling. The instrument developed was a multiple-choice test based on HOTS, covering the cognitive domains of analyzing (C4), evaluating (C5), and creating (C6). Data collection was done through expert validation, instrument trials, and item analysis, which included tests for validity, reliability, difficulty level, discriminating power, and distractor effectiveness. The study results showed that the developed HOTS question instrument has a good level of validity based on expert evaluation, and meets the feasibility criteria in terms of reliability, difficulty, discriminating power, and distractor effectiveness. In addition, implementing the norm-referenced assessment system (PAN) can provide an idea of students' relative abilities within their group.